Kelimpahan Mikroba Tanah Asal Rizosfer Tanaman Sukulen - Zulaika, Aidha; Wijayanti, Dian Rachma; Safari, Wulan Fitriani (Biota, 2021)
Plant host symbiosis is close related to soil microbial abundance. Soil microbial abundance will affect soil quality and fertility, thus will improve plant growth. Studies on soil microbial abundance in succulent plant rhizosphere, especially in Indonesia, are scarce. This study aims to observe soil microorganisms' existence and their abundance on succulent plant rhizosphere. This research used two primary methods to isolate Arbuscule Mycorrhizal Fungi (AMF) and actinomycetes. The spore extraction (soil separating) method was used to obtain AMF spores, followed by the root staining method to observe AMF infection on the plant roots. Serial dilution and pour plate method were used for isolation of Actinomycetes. The isolation results showed a high number of Actinomycetes distribution up to 3.3 x 106 Actinomycetes CFU/g from the plant Echinocactus grusonii, while AMF spores displayed the most elevated number up to 47 spore/25g from the plant Deuterocohnia sp. The percentage of AMF root infection is covered by 27,9% median. AMF identification was based on spore. The result showed an abundance presentation of Actinomycetes in each soil sample. AMF and Actinomycetes existence displayed symbiotic interaction between succulent plants and soil microorganisms. AMF and actinomycetes play the role of endophytes that help the growth of cacti, generally have a dry growing environment, and limited nutrition by this symbiotic interaction. Actinomycetes distribution in rhizospheric soil will increase plant growth-promoting factors activity. Eventually, the implications of research results are to explore the abundance and biodiversity of soil microorganisms from succulent plant rhizosphere that lacked exploration.